Hiring leaders: Inference and disagreement about the best person for the job. Issue 1 (December 2017) - Giannakas, Konstantinos; Fulton, Murray; Awada, Tala
Abstract Hiring is a critical determinant of organizational performance and has received considerable attention in economics where the focus is on identifying who is the best person for the job (an adverse selection problem) and ensuring that the person hired has incentives to behave in a desirable manner (a moral hazard problem). The implicit assumption in this literature is that everyone agrees on what constitutes the "best candidate." In this paper we show that the economics literature fails to recognize that people will generally disagree over "what is best?" Answering this question requires people to make inferences about the environment the organization expects to experience in the future and to match this environment with leader characteristics. Given the idiosyncratic nature of inference, there will be disagreement on the "best person for the job, " even when everyone shares the same goals. The purpose of this paper is to outline why conflict regarding the most desirable person for the job emerges in rapidly changing environments and how this conflict is different from conflict that arises from self-interest and the presence of decision-making biases. The paper shows that conflict from inference, if properly dealt with, can actually improve decision-making, and what can be done to create the right conditions for this to occur. The paper also shows why hiring always involves an element of luck.